2018
DOI: 10.1111/liv.13645
|View full text |Cite
|
Sign up to set email alerts
|

Infections complicating cirrhosis

Abstract: Patients with cirrhosis have a high risk of bacterial infections. Bacterial infections induce systemic inflammation that may lead to organ failure and acute-on-chronic liver failure (ACLF) resulting in a high risk of short term mortality. The early diagnosis and treatment of bacterial infections is essential to improve the patient's prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
129
0
15

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 145 publications
(148 citation statements)
references
References 53 publications
4
129
0
15
Order By: Relevance
“…In addition, about 20% of patients with infection may acquire second infections during the hospitalization . Risk factors for the development of infections are poor liver function, ascites, low protein concentration in ascitic fluid, GI bleeding, and previous infections . About two‐thirds of these infections are diagnosed at admission (within 48 hours), whereas one‐third are nosocomial.…”
Section: Prevalence Type and Clinical Characteristics Of Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, about 20% of patients with infection may acquire second infections during the hospitalization . Risk factors for the development of infections are poor liver function, ascites, low protein concentration in ascitic fluid, GI bleeding, and previous infections . About two‐thirds of these infections are diagnosed at admission (within 48 hours), whereas one‐third are nosocomial.…”
Section: Prevalence Type and Clinical Characteristics Of Infectionsmentioning
confidence: 99%
“…Patients with cirrhosis have a high risk for development of infections and sepsis, which is almost doubled when compared with patients hospitalized for other diseases . The high risk for infections in patients with cirrhosis is due to several factors, namely immune dysfunction, increased intestinal permeability, quantity and quality changes in gut microbiota, and genetic predisposition, contributing to a pathological bacterial translocation from the gut to the systemic circulation …”
mentioning
confidence: 99%
“…(35,37,38) The gut milieu of this population is also adversely affected by multiple antibiotic courses that are often prescribed. (39) Our human trial demonstrated short-term and longterm improvement in cognitive function after antibiotics and FMT, which was not seen in the group that received only standard of care. (9,40) Therefore, our translational results of the pre-FMT and post-FMT stool and supernatant analysis on brain inflammatory expression in GF mice is a highly relevant approach to explore mechanisms and eliminate clinical variables.…”
Section: Discussionmentioning
confidence: 65%
“…However, a substantial proportion of patients with HE recur and have evidence of persistent cognitive impairment despite this standard of care . The gut milieu of this population is also adversely affected by multiple antibiotic courses that are often prescribed . Our human trial demonstrated short‐term and long‐term improvement in cognitive function after antibiotics and FMT, which was not seen in the group that received only standard of care .…”
Section: Discussionmentioning
confidence: 70%
“…Bacterial infections are common in cirrhosis, estimated to occur in 25% to 46% of patients hospitalized with acute decompensation of cirrhosis . The presence of infection triggers a surge of inflammatory response, superimposed on the chronic systemic inflammation related to intestinal dysbiosis, loss of intestinal mucosal integrity, and increased bacterial translocation that is usually present in these patients .…”
mentioning
confidence: 99%